Finding a needle in a haystack - Zoran Mandic (International Association of Physical Chemists (IAPC), 2013)
Book review: Absorption and Drug Development. Solubility, Permeability and Charge State. 2nd Edition. Alex Avdeef, John Wiley & Sons Inc. 2012.